Determinants and moderators of organic food purchase intention. (September 2022) - Eberle, Luciene; Sperandio Milan, Gabriel; Borchardt, Miriam; Medeiros Pereira, Giancarlo; Paula Graciola, Ana
Highlights: Ecological Awareness has a positive relationship with Little Product Knowledge. Conscious Consumption has a positive relationship Consumer Attitude. Little Product Knowledge negatively influences Consumer Attitude. Consumer Attitude positively influences Purchase Intention. Income and consumption frequency moderating Attitude and Purchase Intention. Abstract: Researchers have been investigating consumers' purchase intention towards organic food. In this context, this research aimed to propose, test, and validate a theoretical model that considers ecological awareness, healthy consumption, consumer attitude, and little product knowledge as determinants of the intention to purchase organic food. Furthermore, we aimed to analyze the moderating effect of age, frequency of consumption, family size, and individual income on the relationship between consumer attitude and purchase intention. For this purpose, we implemented a survey from a non-probabilistic convenience sample with 532 Brazilian consumers with access to organic food consumption. For data analysis, structural equation modeling was used to test the proposed theoretical model, allowing a better understanding of the purchase intention of organic food from the consumers' perspective. The results showed that ecological awareness, healthy consumption, consumer attitude, and little product knowledge are determinants of organic food purchase intention and that such determinants could explain 78.8% of the variance of organic food purchase intention. It is also noteworthy that individual income and frequency of consumption have a positive moderating effect on the relationship between consumer attitude and the purchase intention of organic food.